Inter-civilizational issues and the factors affecting interfaith relationships: a study of Muhammad Hamidullah’s contributions - Gilani, Syed Iftikhar Ali; Khaliq, Ahmad; Waheed, Abdul (IIUM Press, 2024)
Interesting issues related to cross civilizations matters for linking the past with future. It becomes more significant when East meets the West. Contrast in civilizations and one’s exposure to this develops a different personality and Dr. Muhammad Hamidullah is one of them who is known for such intellectual contributions that has made an impact on the inter and intra civilisational issues. This paper explores the factors influencing interfaith relationships with a specific focus on the contributions of Dr. Muhammad Hamidullah. In an era of globalisation, multicultural and multi-religious societies are increasingly common. Dr. Hamidullah, having spent a significant portion of his life interacting with followers of various religions, provides valuable insights into fostering inter-civilisational harmony. His scholarly work and personal interactions highlight how different faiths can coexist peacefully within the same society. This study investigates the factors that enhance or hinder interfaith relationships and discusses the societal consequences of interfaith harmony. The research is framed around Dr. Hamidullah’s experiences and contributions, particularly during his time in France, where he engaged with people from diverse religious and cultural backgrounds. By examining his approach to interfaith dialogue and understanding, the paper aims to provide guidance on improving interfaith relations in contemporary society. This study employs a qualitative and narrative research methodology. It focuses on identifying and analysing the factors affecting interfaith harmony by interpreting the teachings and actions of Dr. Muhammad Hamidullah. The narrative approach is used to present real-life examples from his experiences, highlighting the challenges and opportunities in interfaith dialogues. The research is grounded in a detailed analysis of Dr. Hamidullah’s scholarly contributions and personal interactions with people of different faiths, emphasising practical solutions to improve interfaith relationships in today’s globalised world.